ABCB1/MDR1 gene polymorphism and colorectal cancer risk: a meta‐analysis of case–control studies. (20th December 2012) - He, T.; Mo, A.; Zhang, K.; Liu, L.
Abstract Aim ABCB1/MDR1 protein is found in high concentrations on the apical surfaces of colonic epithelial cells. It acts as an efflux pump by transporting toxic endogenous substances, drugs and xenobiotics out of cells. Polymorphisms in the ABCB1/MDR1 gene may either change expression of the ABCB1/MDR1 protein or alter its function, suggesting its possible association with colorectal cancer. Several studies have reported a relationship between ABCB1 gene polymorphisms and colorectal cancer risk, but no consistent conclusion has been reached. We therefore conducted a meta‐analysis to identify any association between the ABCB1 gene and CRC risk. Method PubMed, Embase, Google Scholar, Cbmdisc and CNKI were searched for studies on the relationship of ABCB1/MDR1 gene SNPs and the incidence of colorectal cancer. Eligible articles were included for data extraction. The main outcome was the frequency of ABCB1/MDR1 gene SNPs among cases and controls. Comparison of the distribution of SNPs was performed mainly using Review Manager 5.0. Results Ten, four and two trials were identified that focussed on the ABCB1 gene SNPs rs1045642, rs2032582 and rs3789243, respectively. A total of 3175 cases and 3715 controls were included. The meta‐analysis, stratified by ethnicity or population source, indicated no association between the ABCB1 gene rs1045642 polymorphism and colorectal cancer risk. However, when the study by Bae et al. was removed from the analysis, there was some evidence to indicate a higher T‐allele frequency in Asian colorectal cancer patients (OR = 1.30, 95% CI: 1.02–1.67, P = 0.03). Neither ABCB1 rs2032582 nor ABCB1 rs3789243 indicated an association with colorectal cancer risk. An increased frequency only of the wild‐type combined allele (rs2032582G/rs1045642C) was found in Caucasian patients (OR = 1.22, 95% CI: 1.03–1.44, P = 0.02). Conclusion There is some evidence to indicate an association between ABCB1 rs1045642T and colorectal cancer risk in Asians. Compared with the ABCB1 gene SNPs rs1045642, rs2032582 or rs3789243 alone, combined haplotypes of several SNPs might be a better marker to determine the genetic influence on the susceptibility to colorectal cancer among Caucasians.